Evaluación del precio de venta al público de los equipos de bricolaje y su impacto en la rentabilidad del Comercial "El Turco" Del Cantón Urdaneta en el periodo 2022. - Yánez Yarleque, Miguel Alejandro (2023)
The present work of curricular integration is based on evaluating the retail price that the commercial El Turco establishes in its do-it-yourself equipment and analyzing how it impacts the profitability of the business. The commercial El Turco, located in the Urdaneta canton, whose economic activity is the retail and wholesale sale of do-it-yourself equipment, faces certain difficulties due to the level of competition in the Urdaneta canton. This competition generates pressure, which causes the commercial El Turco to apply commercial strategies in the company and in its retail prices of DIY equipment, which implies a positive impact on the profitability of the business, so it was decided to evaluate the impact that the retail price of DIY equipment generates on the profitability of the commercial "El Turco", Since evaluating this financial indicator is of utmost importance because the company analyzes exhaustively the impact generated by the selling prices of DIY equipment to the public and can make an analysis of the profit margin they have obtained at the end of the period in order to know their economic situation, and thus be able to make optimal financial decisions; In this way it was possible to verify the information by means of the instruments, techniques and research methods that were used.